2016
DOI: 10.1111/bju.13557
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns, testicular loss and disparities in inpatient surgical management of testicular torsion in boys: a population‐based study 1998–2010

Abstract: There has been a gradual decrease in inpatient surgical treatment for both NTT and ATT, presumably as a result of increased outpatient and/or non-operative management of these children. Concerningly, TL patterns have not improved; targeted interventions such as parental and adolescent male health education may lead to timely recognition/intervention in children at-risk for ATT. We noted no regional/racial disparities in contrast to earlier studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The annual incidence of TT has been estimated to be around 0.004% among children <18 years (2). TT may occur at any age, but the vast majority of cases occur after age 10 years with a peak at 12 to 16 years (3). This disease features a dramatic reduction of testicular blood supply due to the torsion of the spermatic cord, with left-sided predominance, and rare bilaterality.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of TT has been estimated to be around 0.004% among children <18 years (2). TT may occur at any age, but the vast majority of cases occur after age 10 years with a peak at 12 to 16 years (3). This disease features a dramatic reduction of testicular blood supply due to the torsion of the spermatic cord, with left-sided predominance, and rare bilaterality.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the 1980s, salvage rates have not improved further [9,10]. Even in 'salvaged' cases, longer-term atrophy remains high in 30-67% of cases [9,10]. A rapid evidence search carried out by the authors of the present study found no published studies evaluating interventions designed to improve salvage rates.…”
Section: Introductionmentioning
confidence: 63%
“…From the 1960s to the 1980s, salvage rates improved from 45% to 67% [8]. However, since the 1980s, salvage rates have not improved further [9,10]. Even in 'salvaged' cases, longer-term atrophy remains high in 30-67% of cases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Challenges still persist at present in ensuring that the incidence of missed testicular torsion is minimized. Sood et al 7 analyzed the temporal trend in the management of testicular torsion between 1998 and 2010 in the United States, using a cohort of over 17,000 patients, and found no improvement in the rate of testicular loss over this period. A number of factors may be involved, and the key to improving outcomes lies in identifying which of these factors are most influential so they can be addressed.…”
Section: Discussionmentioning
confidence: 99%